Use of the research-oriented approach and its technologization in training of tertiary students majoring in philology - Valyukevych, Tetyana; Zinchenko, Olha; Ishchenko, Yevhenii; Artemov, Volodymyr; Nechaiuk, Liudmyla (Institute of Advanced Engineering and Science, 2021)
The study explores how technological advances incorporated into the Philology Studies curriculum could impact students’ research skills and quality of research projects and what students’ and teachers’ impressions of the reshaped research component of the curriculum were. Qualitative and quantitative methods were used. It employed the baseline study, checklist to assess students’ research papers, assessment criteria, and the Triangular Assessment Method to assess papers. The consensus meeting was held to express reasoning for the scores. The semi-structured interview was administered to identify impressions of the reshaped research component of the curriculum of philology. The technological advances incorporated into Philology Studies curriculum improve the research skills and the quality of their research projects. Both students and teachers appreciated the reshaped research component of the curriculum. The analytical software can be successfully incorporated in the corpus analysis-purpose student research. The students found the intervention a challenging experience that ‘pumped up’ their skills. They reported improvement in interpreting corpus using correlations, frequencies, distributions, and collecting information using software to organize it in a professional way. The lecturers agreed that the technology-based instructional model incorporated into Philology Studies curriculum improved both students’ research skills and the quality of their research projects.